Botulinum Toxin Treatment of Cervical Dystonia - Bledsoe, Ian O.; Comella, Cynthia L. (Seminars in Neurology, 2016)
The use of botulinum toxin for the treatment of cervical dystonia (CD) was first reported in 1985. Since then, four commercially available formulations have been approved by the U.S. Food and Drug Administration for use in CD, including three botulinum toxin A formulations and one botulinum toxin B formulation. Recent clinical trials have generally demonstrated good efficacy and tolerability. Commonly reported side effects include dysphagia, muscle weakness, and dry mouth. Secondary nonresponse may develop, but the relationship of detected antibodies to clinical responsiveness remains unclear. Further research is needed into the treatment of complex subtypes of CD and the potential use of alternate botulinum toxin serotypes or subtypes with less immunogenic profiles.
Keywords: cervical dystonia; dystonia; botulinum toxin